2016 17th IEEE International Conference on Mobile Data Management (MDM) 2016
DOI: 10.1109/mdm.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle-Sharing System Analysis and Trip Prediction

Abstract: Abstract-Bicycle-sharing systems, which can provide shared bike usage services for the public, have been launched in many big cities. In bicycle-sharing systems, people can borrow and return bikes at any stations in the service region very conveniently. Therefore, bicycle-sharing systems are normally used as a shortdistance trip supplement for private vehicles as well as regular public transportation. Meanwhile, for stations located at different places in the service region, the bike usages can be quite skewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Therefore, studying the effects of shared bicycles on urban public transportation is an important research topic. The existing research qualitatively analyzed the great contribution of shared bicycles in relieving the pressure on public transportation systems [23][24][25]. Some scholars have analyzed the effects of public bicycle systems on the travel time of public transportation, and the results showed that public bicycle systems improved the efficiency of urban public transport trips [26][27][28].…”
mentioning
confidence: 99%
“…Therefore, studying the effects of shared bicycles on urban public transportation is an important research topic. The existing research qualitatively analyzed the great contribution of shared bicycles in relieving the pressure on public transportation systems [23][24][25]. Some scholars have analyzed the effects of public bicycle systems on the travel time of public transportation, and the results showed that public bicycle systems improved the efficiency of urban public transport trips [26][27][28].…”
mentioning
confidence: 99%
“…Each user may have unique movement styles and preferences that lead to diverse trip frequency, duration, speed, waiting times, motifs, distance, and direction. Meanwhile, the same regularities and patterns are likely to be associated with the same user type: commuters, casual users, tourists, and night workers [12,[71][72][73], for example. If the homogenous users can be grouped into certain clusters, it would be possible to measure cluster predictability level and use their collective trends to make a cluster-based prediction than using non-homogenous of whole users.…”
Section: Bss Individual Mobility Behaviourmentioning
confidence: 99%
“…Other studied data sets are from Chicago [73,80,98,99], Lyon [63,65,74,100], Boston [12,76,80,101], Barcelona [11,70,102], Hangzhou [15,16,103], Brisbane [61,83], Minneapolis [76,104], Vienna [105,106], Denver [76,84], Pisa [64,107], Dublin [14,108], Minnesota [84], Seville [102], Montreal [109] Helsinki [110], Vancouver [111], Nanjing [112], and Castellon [113]. In addition to BSS data, some of those studies also used weather data as a feature of their analyses.…”
Section: Previous Bss Studiesmentioning
confidence: 99%
See 2 more Smart Citations